Metabolomic analysis of Shiga toxin 2a-induced injury in conditionally immortalized glomerular endothelial cells - Patry, Christian; Betzen, Christian; Perez Ortiz, Alba; Tönshoff, Burkhard; Rafat, Neysan (Metabolomics, 2019)
IntroductionShiga toxin 2a (Stx2a) induces hemolytic uremic syndrome (STEC HUS) by targeting glomerular endothelial cells (GEC).ObjectivesWe investigated in a metabolomic analysis the response of a conditionally immortalized, stable glomerular endothelial cell line (ciGEnC) to Stx2a stimulation as a cell culture model for STEC HUS.MethodsCiGEnC were treated with tumor necrosis factor-(TNF)α, Stx2a or sequentially with TNFα and Stx2a. We performed a metabolomic high-throughput screening by lipid- or gas chromatography and subsequent mass spectrometry. Metabolite fold changes in stimulated ciGEnC compared to untreated cells were calculated.Results320 metabolites were identified and investigated. In response to TNFα + Stx2a, there was a predominant increase in intracellular free fatty acids and amino acids. Furthermore, lipid- and protein derived pro-inflammatory mediators, oxidative stress and an augmented intracellular energy turnover were increased in ciGEnC. Levels of most biochemicals related to carbohydrate metabolism remained unchanged.ConclusionStimulation of ciGEnC with TNFα + Stx2a is associated with profound metabolic changes indicative of increased inflammation, oxidative stress and energy turnover.